Which operating mode is the best? Consider different combinations of sales contracts and service methods. (June 2022) - Liu, Hao; Kou, Xiaofei; Liu, Haibin; Gao, Honghu; Zhao, Xinyue
Highlights: The best operating mode is determined based on the strategic game. The deduction rate plays an important role in determining the best operating mode. The best operating mode is only generated when the manufacturer provides service. Shapley value and revenue sharing contract can coordinate the best operating mode. Abstract: According to the different sales contracts and service methods, we propose four supply chain operating modes, that is, the manufacturer provides the service and adopts the wholesale price contract ( MW mode); the retailer provides service and adopts the wholesale price contract ( RW mode); the manufacturer provides service and adopts the consignment contract ( MS mode); the retailer provides service and adopts the consignment contract ( RS mode). In this paper, we develop a dual-channel supply chain consisting of a manufacturer and a retailer to explore the best operating mode for the firms, in which the manufacturer sells products through both online and offline channels. Our analysis shows that there are two thresholds for the deduction rate r 1, r 2, and r 1 < r 2 . If the manufacturer/retailer has absolute power: when r < r 2 / r < r 1, the best mode for the manufacturer/retailer is MS/MW ; when r > r 2 / r > r 1, the best mode for the manufacturer/retailer is MW/MS . In addition, if the manufacturer/retailer decides the service method and the retailer/manufacturer decides the sales contract, when r < r 1 / r < r 2, the best mode for both parties is MW/MS ; when r > r 1 / r > r 2, the best mode for both parties is MS/MW . Furthermore, the Shapley contract and revenue sharing contract are designed to achieve the coordination of the supply chain under the best mode.